2014
DOI: 10.1080/02786826.2014.985780
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Propidium Monoazide Quantitative PCR for Evaluating Performances of Bioaerosol Samplers for Sampling AirborneStaphylococcus aureus

Abstract: Airborne Staphylococcus aureus causes a significant proportion of nosocomial infections. The purpose of this study was to combine real-time quantitative polymerase chain reaction with the DNA-binding agent propidium monoazide (PMA-qPCR) to assess exposures to airborne S. aureus. In this work, we generated a S. aureus aerosol and used our assay to detect viable, airborne S. aureus in a study chamber. The biological collection efficiencies of three samplers (the AGI-30 impinger, BioSampler, and Nuclepore filter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
2
15
1
Order By: Relevance
“…In our chamber study, A. baumannii aerosols collected by the Nuclepore filter were subjected to a combination of three stresses for filter sampling: aerosolization, impaction, and desiccation . The CR values of A. baumannii in the present study were very close to those reported for S. aureus . In addition, CRAB clearly demonstrated greater susceptibility than CSAB to the combination of these three stresses.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In our chamber study, A. baumannii aerosols collected by the Nuclepore filter were subjected to a combination of three stresses for filter sampling: aerosolization, impaction, and desiccation . The CR values of A. baumannii in the present study were very close to those reported for S. aureus . In addition, CRAB clearly demonstrated greater susceptibility than CSAB to the combination of these three stresses.…”
Section: Discussionsupporting
confidence: 75%
“…34 The CR values of A. baumannii in the present study were very close to those reported for S. aureus. 24 In addition, CRAB clearly demonstrated greater susceptibility than CSAB to the combination of these three stresses. The evolution of cells to become CRAB, in contrast to CSAB, resulted in the complete loss of LPS production.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It also could be interesting to study several strains of the same bacterial species to specifically address strain-specific aerobiological stability characteristics. The ambition for the future also involves adopting additional characterization methods, including flow cytometry in combination with membrane integrity and metabolic cell staining (20,45,46) and quantitative PCR in combination with ethidium or propidium monoazide live-dead discrimination techniques (47)(48)(49)(50), as well as the study of multiple strains of the same bacterial species to investigate strain-specific aerobiological stability characteristics.…”
Section: Single-cell Particles and Cell Clusters Produced From Differmentioning
confidence: 99%
“…The pellet of bacteria was washed twice with 1 ml TES buffer (25 mM TrisHCl, 0.1 M EDTA, 25% [wt/vol] saccharose [pH 8]), centrifuged at (5000 × g) for 10 min at 4°C, and then the supernatant was removed. Cell suspensions for propidium mono azide (PMA) staining, the tubes were stained with 10 mg/ml PMA for 5 min in dark place and then transferred to ice and exposed to a 500 W halogen light for 7 min Tseng et al (). Total DNA was extracted by using the Wizard DNA Purification Kit (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%